Self-Testing Is a Feasible and Acceptable Option for Identifying Extra-genital Gonorrhea (GC) and Chlamydia (CT) infections in HIV-Infected Persons. (4th October 2017) - Ganesan, Anuradha; Golden, Dana; Deiss, Robert; O'Bryan, Thomas; Maves, Ryan; Blaylock, Jason M; Okulicz, Jason; Garges, Eric
Abstract: Background: Compliance with guidelines recommending extra-genital testing for GC/CT in HIV-infected men who have sex with men is variable. Proposed barriers to testing, such as patient reluctance and provider discomfort, could be eliminated by self-testing. In this study, we evaluate the feasibility and acceptability of extra-genital self-testing and assess the adequacy of an oral rinse for the diagnosis of GC/CT infections. Methods: HIV-infected subjects receiving care at one of three military treatment facilities participated in this study. Subjects received standardized instructions on sample collection and participated in a questionnaire designed to evaluate acceptability of this method. In addition, all subjects underwent testing by their provider. Gen Probe Aptima Combo 2 assay was used for testing the swabs and the rinse. Results: A total of 148 HIV-infected subjects (median age 43 years, 40% African-Americans and 35% Caucasians) enrolled in the study. Test results are tabulated below. Of the 126 oral rinses tested, 6 (4.7%) tested positive for GC and 1 for CT (0.8%). Of the 6 rinses testing positive for GC, 2 tested negative on concomitantly collected swabs, and 1 swab testing positive for GC was negative on the rinse. Of note, 2 swabs testing positive for GC on self-collection but negative on provider swabs tested positive on the rinse. Over 95% of the subjects indicated that they understood the instructions and had collected the swabs as instructed. Most subjects (≥90%) indicated that they were comfortable collecting the swabs and oral rinses at home. Approximately15% of the subjects preferred that their providers collected the swabs. Conclusion: In this study, self-collected samples yielded more positive results than provider collected samples, and the performance of oral rinses and pharyngeal swabs were similar. Our results suggest self-testing is a feasible and acceptable method for collecting extra-genital samples. Adoption of self-testing could improve compliance with the guidelines. Disclosures: All authors: No reported disclosures.